2008
DOI: 10.1093/brain/awn140
|View full text |Cite
|
Sign up to set email alerts
|

Increase in prefrontal cortical volume following cognitive behavioural therapy in patients with chronic fatigue syndrome

Abstract: Chronic fatigue syndrome (CFS) is a disabling disorder, characterized by persistent or relapsing fatigue. Recent studies have detected a decrease in cortical grey matter volume in patients with CFS, but it is unclear whether this cerebral atrophy constitutes a cause or a consequence of the disease. Cognitive behavioural therapy (CBT) is an effective behavioural intervention for CFS, which combines a rehabilitative approach of a graded increase in physical activity with a psychological approach that addresses t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
137
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(156 citation statements)
references
References 51 publications
3
137
0
2
Order By: Relevance
“…Furthermore, cognitive behavioral therapy (CBT) techniques have been correlated with neuroplastic changes in different pathological conditions using neuroimaging techniques (Linden 2006;de Lange et al 2008). The potential of MRI techniques to measure CBT impact on brain architecture has been shown also in a recent study on chronic fatigue syndrome patients, in which CBT has been correlated with prefrontal cortex gray matter modulation (de Lange et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, cognitive behavioral therapy (CBT) techniques have been correlated with neuroplastic changes in different pathological conditions using neuroimaging techniques (Linden 2006;de Lange et al 2008). The potential of MRI techniques to measure CBT impact on brain architecture has been shown also in a recent study on chronic fatigue syndrome patients, in which CBT has been correlated with prefrontal cortex gray matter modulation (de Lange et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, an overlap exists in components of the pain neuromatrix and brain regions involved in cognitive processing (e.g., anterior cingulate cortex, insular cortex, periaqueductal gray) (14). Together with the demonstrated changes in neuroplasticity [e.g., gray matter volume reduction (15)(16)(17)] and dysregultated neurochemistry [e.g., decreased levels of brain-derived neurotrophic factor (18), increased levels of gamma-aminobutric acid (19), increased levels of pro-inflammatory cytokines (20)], these pain-induced changes in resource utilization may (in part) explain (pain-related) cognitive impairment in chronic pain patients.…”
Section: Participants and Assessmentsmentioning
confidence: 99%
“…One intervention study reported increased gray matter (GM) volume in the lateral frontal lobe in CFS patients who underwent cognitive behavioral therapy (CBT) 10 months after baseline 10. The authors interpreted this change to be a result of CBT.…”
mentioning
confidence: 99%